2020
DOI: 10.1136/practneurol-2019-002415
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral venous thrombosis: a practical guide

Abstract: All neurologists need to be able to recognise and treat cerebral venous thrombosis (CVT). It is difficult to diagnose, partly due to its relative rarity, its multiple and various clinical manifestations (different from ‘conventional’ stroke, and often mimicking other acute neurological conditions), and because it is often challenging to obtain and interpret optimal and timely brain imaging. Although CVT can result in death or permanent disability, it generally has a favourable prognosis if diagnosed and treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
149
0
31

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(180 citation statements)
references
References 64 publications
0
149
0
31
Order By: Relevance
“…The reported frequency of anemia was 3.2% by Duman et al 26 and 9.2% Ferro et al 16 A case-control study reported a figure of 27% in patients with CVT compared with 6.5% in the control group )p<0.001(. 34,36 This study detected a much higher frequency of anemia of 30%, which is of significance as it can be prevented.…”
mentioning
confidence: 52%
“…The reported frequency of anemia was 3.2% by Duman et al 26 and 9.2% Ferro et al 16 A case-control study reported a figure of 27% in patients with CVT compared with 6.5% in the control group )p<0.001(. 34,36 This study detected a much higher frequency of anemia of 30%, which is of significance as it can be prevented.…”
mentioning
confidence: 52%
“…населения в год [2,3]. ЦВТ служит причиной 0,5-1,0% поступлений в инсультный центр [4]. Женщины в возрасте от 31 года до 50 лет характеризуются более высокой заболеваемостью -2,8 на 100 тыс.…”
unclassified
“…населения в год [5]. Средний возраст пациентов соответствует 33 годам, женщины страдают в 1,5-3 раза чаще [4,5].Ф а к т о р ы р и с к а и а с с о ц и и р о в а н н ы е к л и н и ч е с к и е с о с т о я н и я Состояния, ассоциированные с ЦВТ, подразделяют на предрасполагающие (генетические протромботические заболевания, антифосфолипидный синдром, рак и др.) и провоцирующие (оральные контрацептивы, инфекции, препараты с протромботическим эффектом; табл.…”
unclassified
See 2 more Smart Citations